Antioxidant Status of Broiler Chickens Fed Diets Supplemented with Vinification By-Products: A Valorization Approach - Alexandros Mavrommatis; Elisavet Giamouri; Eleni D. Myrtsi; Epameinondas Evergetis; Katiana Filippi; Harris Papapostolou; Sofia D. Koulocheri; Evangelos Zoidis; Athanasios C. Pappas; Apostolis Koutinas; Serkos A. Haroutounian; Eleni Tsiplakou (MDPI AG, 2021)
Vinification by-products display great potential for utilization as feed additives rich in antioxidant compounds. Thus, the effect of dietary ground grape pomace (GGP), wine lees extract rich in yeast cell walls (WYC), and grape stem extracts (PE) on the relative expression of several genes involved in liver oxidative mechanisms and the oxidative status of the blood and breast muscle of broiler chickens was investigated. In total, 240 one-day-old as hatched chicks (Ross 308) were assigned to four treatments, with four replicate pens and 15 birds in each pen. Birds were fed either a basal diet (CON) or a basal diet supplemented with 25 g/kg GGP, or 2 g/kg WYC, or 1 g starch including 100 mg pure stem extract/kg (PE) for 42 days. The polyphenolic content of vinification by-products was determined using an LC-MS/MS library indicating as prevailing compounds procyanidin B1 and B2, gallic acid, caftaric acid, (+)-catechin, quercetin, and trans-resveratrol. Body weight and feed consumption were not significantly affected. The relative transcript level of GPX1 and SOD1 tended to increase in the liver of WYC-fed broilers, while NOX2 tended to decrease in the PE group. SOD activity in blood plasma was significantly increased in WYC and PE compared to the CON group. The total antioxidant capacity measured with FRAP assay showed significantly higher values in the breast muscle of PE-fed broilers, while the malondialdehyde concentration was significantly decreased in both WYC- and PE-fed broilers compared to the CON group. The exploitation of vinification by-products as feed additives appears to be a promising strategy to improve waste valorization and supply animals with bioactive molecules capable of improving animals' oxidative status and products' oxidative stability.